2013
DOI: 10.1074/jbc.m113.491530
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Inhibition Mechanisms of Adalimumab and Infliximab in Treating Tumor Necrosis Factor α-Associated Diseases from a Molecular View

Abstract: Background:The epitope and the TNF␣ inhabitation mechanism of Adalimumab remain unclear. Results: The crystal structure of the TNF␣ in complex with Adalimumab is reported at a resolution of 3.1 Å. Conclusion:The epitope of Adalimumab provided information that Adalimumab may have clinical advantage compared with Infliximab. Significance: These data reveal the Adalimumab's mechanism of TNF␣ inhibition and its advantages compared with other TNF inhibitors in clinical practice. TNF␣-targeting therapy with the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
137
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(160 citation statements)
references
References 35 publications
6
137
0
Order By: Relevance
“…Most of these side effects were mild or moderate infusion reactions, which were sometimes overweighed and resulted in earlier switches than it would have been necessary. But these side effects, and of course the secondary loss of efficacy, can be explained by the unique chemical structure of this drug (25). The chimeric monoclonal antobody induces production of anti-drug antibodies more intensively than the humanised ones (adalimumab and golimumab) and the receptor fusion protein etanercept.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these side effects were mild or moderate infusion reactions, which were sometimes overweighed and resulted in earlier switches than it would have been necessary. But these side effects, and of course the secondary loss of efficacy, can be explained by the unique chemical structure of this drug (25). The chimeric monoclonal antobody induces production of anti-drug antibodies more intensively than the humanised ones (adalimumab and golimumab) and the receptor fusion protein etanercept.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we report the crystal structure of the antibody adalimumab Fab with the EFab domain substitution. In comparison with the previously reported adalimumab Fab and IgE Fc structures, 18,19 the adalimumab EFab shows a high degree of similarity in the variable domains. However, clear differences in the relative domain orientation of variable domains with respect to constant domains are observed that do not appear to have a detrimental effect on target antigen binding.…”
Section: Introductionmentioning
confidence: 49%
“…The VH and VL domains exhibit typical geometry and the overall variable domain structure within the framework regions and complementarity-determining regions is very similar between the adalimumab EFab and adalimumab Fab (PDB id: 4NYL, 3WD5) (Figure 5A). 19 A superposition of the VH and VL domains of EFab and Fab show a root mean square deviation (rmsd) of 0.37 Å (Cα atoms only) (Figure 5B), demonstrating the high structural similarity. In contrast, when the Cϵ2 domains of the EFab are superimposed to the Cϵ2 domains of the IgE Fc (PDB id: 2WQR) 16 the rmsd of the Cα atoms is 1.32 Å, indicating less structural similarity (Figure 5B).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, comparing the epitopes of different antibodies to the same antigen has garnered significant interest in the field of antibody engineering and targeted therapy. For example, the comparison of the different epitopes of adalimumab and infliximab in complex with TNF using crystallography provided direct evidence of the adalimumab epitope as well as information on a molecular level to further understand the clinical advantages of adalimumab versus infliximab therapy (Hu et al, 2013). Thus, we launched a crystallographic study to investigate the precise epitope of HER3 recognized by 9E12.…”
Section: Introductionmentioning
confidence: 99%